2010
DOI: 10.1016/j.jfludis.2010.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among linguistic processing speed, phonological working memory, and attention in children who stutter

Abstract: Relatively recently, experimental studies of linguistic processing speed in children who stutter (CWS) have emerged, some of which suggest differences in performance among CWS compared to children who do not stutter (CWNS). What is not yet well understood is the extent to which underlying cognitive skills may impact performance on timed tasks of linguistic performance. The purpose of this study was to explore possible relationships between measures of linguistic processing speed and two aspects of cognition: p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 71 publications
6
66
1
3
Order By: Relevance
“…The nonsignificant overall group differences in distractibility are consistent with findings reported by some researchers (e.g., Anderson & Wagovich, 2010;Eggers et al, 2010) but not others (e.g., Anderson et al, 2003;Karrass et al, 2006). Perhaps such equivocal findings relate to between-studies differences in methodology (e.g., caregiver reports vs. experimental paradigms).…”
Section: Between-groups Differences In Distractibilitysupporting
confidence: 88%
See 1 more Smart Citation
“…The nonsignificant overall group differences in distractibility are consistent with findings reported by some researchers (e.g., Anderson & Wagovich, 2010;Eggers et al, 2010) but not others (e.g., Anderson et al, 2003;Karrass et al, 2006). Perhaps such equivocal findings relate to between-studies differences in methodology (e.g., caregiver reports vs. experimental paradigms).…”
Section: Between-groups Differences In Distractibilitysupporting
confidence: 88%
“…Several researchers have compared the attentional processes of preschool-age CWS and CWNS using caregiver reports or various experimental paradigms, and findings have been inconsistent (Anderson et al, 2003;Eggers et al, 2010Eggers et al, , 2012Embrechts et al, 2000;Felsenfeld et al, 2010;Karrass et al, 2006;Schwenk, Conture, & Walden, 2007). Some have reported that CWS tend to be less distractible (e.g., Anderson et al, 2003) and exhibit poorer attention regulation compared with CWNS (e.g., Karrass et al, 2006), whereas others have reported no between-groups differences in attentional processes (e.g., Anderson & Wagovich, 2010). Such inconsistencies may relate to the methodological differences across studies (e.g., using various parent questionnaires vs. experimental paradigms), making it difficult to directly compare findings.…”
Section: Attention and Childhood Stutteringmentioning
confidence: 99%
“…1 In particular, there has been recent focus on the area of attentional control in CWS (Anderson & Wagovich, 2010;Chou, 2014;Eggers, De Nil, & Van den Bergh, 2010Felsenfeld, van Beijsterveldt, & Boomsma, 2010;Johnson, Conture, & Walden, 2012;Kaganovich, Wray, & Weber-Fox, 2010;Karrass et al, 2006;Schwenk, Conture, & Walden, 2007). Some of these studies have used parent or teacher questionnaires, most of them finding that CWS are rated less well than CWNS on aspects of attention (Eggers et al, 2010;Felsenfeld et al, 2010;Karrass et al, 2006;cf.…”
Section: Response Inhibition In Cwsmentioning
confidence: 99%
“…The interest in the interaction between factors of language and speech fluency in children who stutter has grown in the last 20 years 10 . Studies that investigated the abilities and disorders of language in children, who stutter, indicated that this group compared with those who do not stutter, had presented lower scores on several indices of receptive and expressive language [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] .…”
Section: Methodsmentioning
confidence: 99%